Fuzzy communication for guided loop scheduling in multicomputers - Chien-Ming Cheng; Kai Hwang (Parallel Processing Symposium, 8th International (IPPS '94, 1994)
We propose the use of guided loop scheduling and fuzzy communications to map shared-variable communications into message passing operations among multicomputers. The mapping mechanism converts scalar message passing operations into multiple broadcast or multiple multicast operations. The proposed method is evaluated by both simulation experiments and theoretical analysis. The performance results, considering both communication and computation, are reported for mapping two distributed matrix algorithms. Simulated benchmark results demonstrate improved performance and minimized execution time. The proposed method offers the potential to take advantage of the programmability of shared-memory systems and the scalability of distributed-memory systems.< >